INOVASI ALAT UKUR KECEPATAN LARI BERBASIS MICROCONTROLLER DAN WIRELESS NETWORK DENGAN INTERFACING PERSONAL COMPUTER SYSTEM - Ramadhan, Chaerul Umam (2014)
This study of speed measuring devices based on microcontroller and wireless network with interfacing personal computer system was conducted to exercise the speed distance time calculation using stopwatch without recording time automatically; therefore, the establishment of the simple, practical, effective and efficient tools in domestic appliance is needed. In the presence of speed measuring devices based on microcontroller and wireless network with interfacing personal computer system in this country can facilitate the testee to control the test easily and practically. One of the purpose to make this research is to provide hardware and software to measure runner's speed based on microcontroller and wireless networking with interfacing personal computer system. This instrument is one of a test to calculate runner's time record. The main function of the instrument is guiding testee in his test which monitoring tester with automatic time record. The method of this research is adapted from design method research and development (Sugiono 2013) including these steps: (1) Potency and problem (2) Gathering information (3) Product design (4) Design Validation (5) Design correction (6) Product Experiment which done with field experiment significantly running well, and the program of the instrument work just like stopwatch do.